Neuroscience-Based Change Management: Transforming Islamic Boarding School Culture and Advancing Arabic Learning Models - MOHAMMAD JAILANI, MOHAMMAD JAILANI (Balai Diklat Keagamaan Denpasar, 2025)
The impression of Islamic and scientific culture within Islamic boarding schools is increasingly essential in today’s era of rapid technological advancement, where the potential of students is growing and becoming increasingly dynamic. This study explores the need for change management to enhance students’ capabilities and development in achieving better learning outcomes. The research was conducted at MBS Pleret, Yogyakarta, with informants comprising one religious teacher and ten students. A qualitative case study approach was employed, with data collected through interviews and observations. Data analysis involved processes of reduction, display, and verification. The findings indicate that the theory- and practice-based learning process at MBS Muhammadiyah Pleret, Yogyakarta, is supported by effective learning change management. The study revealed that students’ learning outcomes and overall development showed significant improvement compared to previous results. The implications of this research highlight the benefits for educators, who are supported by the integration of change management and knowledge management strategies, in enhancing students’ academic achievements. The data, collected every six months, shows a notable growth in students' learning potential, particularly through the application of neuroscience principles. Additionally, the culture of the pesantren significantly influences the behavior and lifestyle of both students (santri) and religious teachers. The findings suggest that implementing change management in Islamic boarding schools enhances learning outcomes, managerial knowledge, and cultural aspects of school management. However, the research did not establish a significant correlation between change management and knowledge management, suggesting the need for further investigation to understand their interrelationship.